Implementation of Mental Health Support System and Its Impact on Organizational Performance of Large Hospitals in Medan: The Mediating Role of Employee Well - Being - Siti Normi Sinurat; Kristanty M N Nadapdap; Sondang Ni Bulan Marbun; M Doddy Simanjuntak; Maludin Panjaitan (Program Studi Akuntansi Universitas Simalungun, 2025)
This research investigates how Mental Health Support System (MHSS) implementation functions as a comprehensive intervention mechanism for enhancing organizational performance through improved employee well-being in large hospitals in Medan. Drawing upon Job Demands-Resources (JD-R) theory, Conservation of Resources (COR) theory, and organizational support theory, this study examines how mental health support systems create value through improved employee psychological well-being and reduced work-related stress among healthcare workers. Using Structural Equation Modeling with Partial Least Squares (PLS-SEM) analysis on 8 large hospitals in Medan (385 healthcare worker observations, 2023-2024), the research demonstrates that mental health support system implementation significantly enhances employee well-being (β = 0.692, p < 0.001) and directly improves organizational performance (β = 0.458, p < 0.001). Employee well-being substantially mediates the relationship between mental health support systems and organizational performance (indirect effect = 0.389, p < 0.001, VAF = 45.9%). The model explains 61.8% of employee well-being variance and 68.3% of organizational performance variance. This study provides comprehensive empirical evidence of how mental health support systems transform healthcare workplace environments and operational effectiveness in hospital settings